Kemandirian Perilaku Peserta Didik dalam Pemilihan Jurusan dan Implikasinya terhadap Pelayanan Bimbingan dan Konseling - Fajaria, Deprina; Marjohan, Marjohan; Sukmawati, Indah (Konselor, 2013)
Abstract: The independence of behavior is individual who was able in making decisions, not influenced by others, and have the confidence. In fact there are many students confused and follow some of their friends in choosing majors. The purpose of this study illustrate the independence of the decision-making behavior, not influenced by others, and have the confidence in choosing majors. This type of research is descriptive quantitative. Population of 180 people and 64 people samples of learners. The results of independence behavior of learners in choosing majors categorized quite independent.Â Â Keyword: Independence behaveÂ